An Analysis of Blind Signature Schemes - Anna Vasilievna Epishkina; Mikhail Yaroslavovich Shimkiv (Безопасность информационных технологий, 2015)
The purpose of the article was to investigate blind signature schemes, to propose generalized scheme and to obtain its characteristics. The homomorphism of El Gamal scheme was evaluated. Some properties of partial blind signatures and blind signatures based on elliptic curves were estimated. The topic of further work was given.